Physiologic and metabolic characterization of a new marine isolate (BM39) of Pantoea sp. producing high levels of exopolysaccharide - Silvi Silvia; Barghini Paolo; Aquilanti Arianna; Juarez-Jimenez Belen; Fenice Massimiliano (Microbial Cell Factories, 2013)
Abstract Background Marine environments are the widest fonts of biodiversity representing a resource of both unexploited or unknown microorganisms and new substances having potential applications. Among microbial products, exopolysaccharides (EPS) have many physiological functions and practical applications. Since EPS production by many bacteria is too scarce for practical use and only few species are known for their high levels of production, the search of new high EPS producers is of paramount importance. Many marine bacteria, that produce EPS to cope with strong environmental stress, could be potentially exploited at the industrial level. Results A novel bacterium, strain BM39, previously isolated from sediments collected in the Tyrrhenian Sea, was selected for its production of very high levels of EPS. BM39 was affiliated to Pantoea sp. (Enterobacteriaceae) by 16S rRNA gene sequencing and biochemical tests. According to the phylogenetic tree, this strain, being quite far from the closest known Pantoea species (96% identity with P. agglomerans and P. ananatis) could belong to a new species. EPS production was fast (maximum of ca. 21 g/L in 24 h on glucose medium) and mainly obtained during the exponential growth. Preliminary characterization, carried out by thin layer and gel filtration chromatography, showed that the EPS, being a glucose homopolymer with MW of ca. 830 kDa, appeared to be different from those of other bacteria of same genus. The bacterium showed a typical slightly halophilic behavior growing optimally at NaCl 40 ‰ (growing range 0-100 ‰). Flow cytometry studies indicated that good cell survival was maintained for 24 h at 120 ‰. Survival decreased dramatically with the increase of salinity being only 1 h at 280 ‰. The biochemical characterization, carried out with the Biolog system, showed that MB39 had a rather limited metabolic capacity. Its ability, rather lower than that of P. agglomerans, was almost only confined to the metabolization of simple sugars and their derivatives. Few alcohols, organic acids and nitrogen compounds were partially used too. Conclusions Strain BM39, probably belonging to a new species, due to its remarkable EPS production, comparable to those of known industrial bacterial producers, could be suggested as a new microorganism for industrial applications.